INTERLEUKIN-6 PROFILE IN EARLY POSTOPERATIVE PERIOD AFTER KIDNEY TRANSPLANTATION - A. V. Vatazin; A. B. Zulkarnaev; E. E. Kruglov; P. V. Astakhov; M. Krstic; K. K. Gubarev; I. A. Vasilenko; D. V. Artemov (Вестник трансплантологии и искусственных органов, 2013)
Aim. To study the profile of IL-6 in the early postoperative period after kidney transplantation and the factors that affect concentration of this cytokine. Methods and results. 28 kidney recipients were included in the study. It has been found that in most patients after surgery IL-6 was released, and the absence of such a reaction was a poor prognostic sign. Rate of increasing of the concentration and form of its curve within the first postoperative day depended on the length of preservation, warm ischemia time, type of donor, and differed in recipients with normal and delayed initial graft function. Conclusion. Further study of the role of circulating factors in kidney transplantation would improve patient outcomes.